Targeted lung cancer screening selects individuals at high risk of cardiovascular disease. (October 2018) - Balata, H.; Blandin Knight, S.; Barber, P.; Colligan, D.; Crosbie, E.J.; Duerden, R.; Elton, P.; Evison, M.; Greaves, M.; Howells, J.; Irion, K.; Karunaratne, D.; et al.
Highlights: 93% participants at high risk of cardiovascular disease (CVD) (QRISK2 score ≥10%). 1 in 3 of all screening attendees at high risk of CVD but not taking a statin. Those screened had double the CVD risk than controls (21.1% vs. 10.3%, p < 0.001). And 10-times more likely to be high risk than controls (OR 10.2; 95% CI 7.3–14.0). Lung cancer (PLCOM2012 ) and CVD risk (QRISK) scores correlated (r = 0.26, p < 0.001). Abstract: Background: Cardiovascular disease (CVD) is a major cause of morbidity and mortality in populations eligible for lung cancer screening. The aim of this study was to determine whether a brief CV risk assessment, delivered as part of a targeted community-based lung cancer screening programme, was effective in identifying individuals at high risk who might benefit from primary prevention. Methods: The Manchester Lung Screening Pilot consisted of annual low dose CT (LDCT) over 2 screening rounds, targeted at individuals in deprived areas at high risk of lung cancer (age 55–74 and 6-year risk ≥1.51%, using PLCOM2012 risk model). All participants of the second screening round were eligible to take part in the study. Ten-year CV risk was estimated using QRISK2 in participants without CVD and compared to age (±5 years) and sex matched Health Survey for England (HSE) controls; high risk was defined as QRISK2 score ≥10%. Coronary artery calcification (CAC) was assessed on LDCT scans and compared to QRISK2 score. Results: Seventy-seven percent (n= 920/1, 194) of screening attendees were included in the analysis; mean age 65.6 ± 5.4 and 50.4% female. QRISK2 and lung cancer risk (PLCOM2012 ) scores were correlated (r = 0.26, p < 0.001). Median QRISK2 score was 21.1% (IQR 14.9–29.6) in those without established CVD (77.6%, n = 714/920), double that of HSE controls (10.3%, IQR 6.6–16.2; n = 714) (p < 0.001). QRISK2 score was significantly higher in those with CAC (p < 0.001). Screening attendees were 10-fold more likely to be classified high risk (OR 10.2 [95% CI 7.3–14.0]). One third (33.7%, n = 310/920) of all study participants were high risk but not receiving statin therapy for primary CVD prevention. Discussion: Opportunistic CVD risk assessment within a targeted lung cancer screening programme is feasible and is likely to identify a very large number of individuals suitable for primary prevention.